2018
DOI: 10.1371/journal.pone.0194206
|View full text |Cite
|
Sign up to set email alerts
|

Tis21-gene therapy inhibits medulloblastoma growth in a murine allograft model

Abstract: Medulloblastoma (MB), the tumor of the cerebellum, is the most frequent brain cancer in childhood and a major cause of pediatric mortality. Based on gene profiling, four MB subgroups have been identified, i.e., Wnt or Sonic Hedgehog (Shh) types, and subgroup 3 or 4. The Shh-type MB has been shown to arise from the cerebellar precursors of granule neurons (GCPs), where a hyperactivation of the Shh pathway leads to their neoplastic transformation. We have previously shown that the gene Tis21 (PC3/Btg2) inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…These data suggest that Piwil1 may help maintain stemness at least in part through Olig2. Silencing Piwil1 also reduced expression of BTG2, the loss of which promotes tumorigenesis in leukemia, medulloblastoma, and oligodendroglioma by regulating differentiation ( Appolloni et al, 2012 ; Dolezal et al, 2017 ; Kuiper et al, 2007 ; Mullighan et al, 2007 ; Presutti et al, 2018 ). In mouse models of GBM, we found that tumors in which Piwil1 was silenced exhibited increased BTG2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that Piwil1 may help maintain stemness at least in part through Olig2. Silencing Piwil1 also reduced expression of BTG2, the loss of which promotes tumorigenesis in leukemia, medulloblastoma, and oligodendroglioma by regulating differentiation ( Appolloni et al, 2012 ; Dolezal et al, 2017 ; Kuiper et al, 2007 ; Mullighan et al, 2007 ; Presutti et al, 2018 ). In mouse models of GBM, we found that tumors in which Piwil1 was silenced exhibited increased BTG2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the family-related gene PC3 TIS21/BTG2 is an MB suppressor, as its overexpression inhibits the proliferation and facilitates the differentiation of neoplastic GCPs (40,41). In fact, we found that in a mouse model of spontaneous MB, PC3 TIS21/BTG2 deletion causes a great increase of tumor frequency due to a deficit of GCP migration (42,43).…”
Section: Introductionmentioning
confidence: 80%
“…In this regard, we have already identified two molecules that act as tumor suppressors of MB, PC3 TIS21/BTG2 (40,41) and Cxcl3 (74). Then, in this report, we investigated the role in the MB pathogenesis of the PC3 TIS21/BTG2 -related gene Btg1, which we have previously shown to be required for the development and function of the cerebellum by operating basically as a negative regulator of the proliferation of cerebellar cell precursors (GCPs) through inhibition of cyclin D1 (12).…”
Section: Discussionmentioning
confidence: 99%
“…Primers for TATA-box binding protein (TBP) and eukaryotic translation elongation factor 2 (eEF2) were used as internal controls as previously described [57][58][59]. qPCR conditions were as follows: 95˚C for 5 minutes followed by 49 cycles of 95˚C for 10 seconds, 60˚C for 15 seconds, 72˚C for 5 seconds.…”
Section: Reverse Transcription Quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%